Validity and reliability study of the mathematics anxiety scale involving teachers and prospective teachers - (:unkn) unknown (ANI YAYINCILIK, 2008)
Problem Statement: Mathematics is a significant part of education throughout the world. The nature of mathematics typically induces anxiety. Mathematical anxiety can be defined as an irrational dread of mathematics that interferes with manipulating numbers and solving mathematical problems within a variety of everyday life and academic situations. The most significant issue related to the determination of mathematics anxiety is the development of tools that measure this anxiety. There are those who have attempted to measure mathematics anxiety with tools based on self-report techniques, like other personal characteristics. In this scope, while there are various measurement tools, mathematical anxiety scales developed in different scopes (daily life, professional life, etc.) for different samples (children, adults, etc.) are still required. For this reason, the problem of research is that there is no mathematics anxiety scale developed for teachers and prospective teachers who must use mathematics in their professional life for different purposes and on different levels. Purpose of Study: Considering the state of the problem, the aim of this research is to develop a toot that measures mathematics anxiety in teachers and prospective teachers. Methods: In this study designed to develop a mathematics anxiety scale in teachers and prospective teachers, factor analysis and discrimination analyses in the scope of validity studies and item remainder analyses and internal consistency analyses in the scope of reliability analyses were calculated. Findings and Results: As a result of the research, a mathematical anxiety scale composed of 39 items and seven sub-scales and explaining 59.23% of the total variance was developed. Since the scale relates to teachers and prospective teachers, it is called MAST (Mathematics Anxiety Scale toward Teachers). Sub-scales included in the scale were named Mathematics Understanding Anxiety, Mathematics Teaching Anxiety, Problem Solving Anxiety, Arithmetical Operations Anxiety, Mathematical Self-Adequacy Anxiety, Mathematical Interpretation Anxiety, Making Mathematical Mistakes Anxiety. Cronbach alpha internal consistency coefficient of the whole scale was found to be .95. Considering the results obtained, it is understood that MAST is a valid and reliable tool used to determine mathematics anxiety of teachers and prospective teachers. Recommendations: MAST can be used in researches to be conducted to determine mathematical anxiety of teachers and prospective teachers in different fields.
Keywords: mathematical anxiety; mathematical anxiety scale; teachers; prospective teachers